Existenz von invarianten Finslerschen Metriken in homogenen Räumen mit linearer Isotropiegruppe tensorischen Typus, II - Jonušauskas, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Ионушаускас. Существование инвариантных финслеровых метрик в однородных пространствах с линейной группой изотропии тензорного типа. IIA. Jonušauskas. Invariantiškų Finslerio metrikų egzistencija homogeninėse erdvėse su tenzorinio tipo tiesine izotropijos grupe. II